Pulsatilla saponin A Inhibits Proliferation and Induces Apoptosis in Diffuse Large Bcell Lymphoma Cells through the JAK2/STAT3 Signaling Pathway - Liu, Ning; Zhan, Xinzhuo; Bai, Jie; Yu, Hui; Chen, Xiaoli; Kong, Xiangtu; Ni, Haiwen (Anti-Cancer Agents in Medicinal Chemistry, 2023)
Objectives: This study aimed to investigate the performance of Pulsatilla saponin A (PsA) in diffuse large B-cell lymphoma (DLBCL) cells. Methods: Proliferation, ELISA, apoptosis, cell cycle analysis, and assays were carried out to detect the growth and apoptosis in DLBCL cells. Western blotting was used to identify the change in the protein. Results: In cell assays, PsA significantly inhibited the growth and apoptosis in DLBCL cells. The IL-10 and TNF-α of OCI-LY10 and U2932 cells were reduced after 24 h PsA treatment. Bax, cleaved PARP, and cleaved Caspase-3 were increased, while Bcl-2 and C-Myc decreased after PsA treatment. IL-10 may regulate the expression of C-Myc protein in cells by activating the JAK2/STAT3 signaling pathway. PsA can inhibit the overexpression of p-JAK2 and p- STAT3 signaling pathways induced by IL-10 stimulants. The proliferation and apoptosis induced by PsA were confirmed in DLBCL cells. Conclusion: Our findings revealed that PsA may exert its antitumor effect by causing G1 arrest and apoptosis in DLBCL cells. The mechanism of PsA regulating apoptosis in DLBCL cells is probably through the JAK2/STAT3 signaling pathway in vitro.
Keywords: diffuse large B-cell lymphoma (DLBCL)